2012
DOI: 10.1002/gps.3904
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and psychological subsyndromes in Alzheimer's disease using the Neuropsychiatric Inventory

Abstract: This review represents the first attempt to systematically evaluate evidence coming from factor analyses exploring the internal structure of the NPI in order to facilitate the identification of neuropsychiatric syndromes in AD patients. The NPI may support the definition of behavioral subsyndromes in AD. The evaluation of neuropsychiatric subsyndromes should always take into account the main potential confounders, such as age, severity of disease, and concomitant pharmacological treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
88
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 40 publications
12
88
3
2
Order By: Relevance
“…This NPS-class is similar to the symptom pattern commonly reported in studies of MCI samples [5,8,19,24,39,40], and also the 'affective' cluster reported in studies of dementia samples [18]. In our study, 28% of all those with dementia (n = 11) and 19% of those with MCI (n = 25) were classified as having an affective/low comorbidity NPS pattern.…”
Section: Clusters Of Neuropsychiatric Symptomssupporting
confidence: 88%
See 4 more Smart Citations
“…This NPS-class is similar to the symptom pattern commonly reported in studies of MCI samples [5,8,19,24,39,40], and also the 'affective' cluster reported in studies of dementia samples [18]. In our study, 28% of all those with dementia (n = 11) and 19% of those with MCI (n = 25) were classified as having an affective/low comorbidity NPS pattern.…”
Section: Clusters Of Neuropsychiatric Symptomssupporting
confidence: 88%
“…This syndrome included high prevalence of agitation, disinhibition and irritability-a cluster that has been reported in dementia samples, and in conjunction with aberrant motor behavior [18]. Its low prevalence in the sample is also consistent with the literature.…”
Section: Clusters Of Neuropsychiatric Symptomssupporting
confidence: 86%
See 3 more Smart Citations